Inhibition of Lysyl Oxidase and Lysyl Oxidase-Like Enzymes Has Tumour-Promoting and Tumour-Suppressing Roles in Experimental Prostate Cancer - Nilsson, Maria (Sci Rep, 2016)
Lysyl oxidase (LOX) and LOX-like (LOXL) enzymes are key players in extracellular matrix deposition and maturation. LOX promote tumour progression and metastasis, but it may also have tumour-inhibitory effects. Here we show that orthotopic implantation of rat prostate AT-1 tumour cells increased LOX and LOXLs mRNA expressions in the tumour and in the surrounding non-malignant prostate tissue. Inhibition of LOX enzymes, using Beta-aminopropionitrile (BAPN), initiated before implantation of AT-1 cells, reduced tumour growth. Conversely, treatment that was started after the tumours were established resulted in unaffected or increased tumour growth. Moreover, treatment with BAPN did not suppress the formation of spontaneous lymph node metastases, or lung tumour burden, when tumour cells were injected intravenously. A temporal decrease in collagen fibre content, which is a target for LOX, was observed in tumours and in the tumour-adjacent prostate tissue. This may explain why early BAPN treatment is more effective in inhibiting tumour growth compared to treatment initiated later. Our data suggest that the enzymatic function of the LOX family is context-dependent, with both tumour-suppressing and tumour-promoting properties in prostate cancer. Further investigations are needed to understand the circumstances under which LOX inhibition may be used as a therapeutic target for cancer patients.